KONTRIBUSI REMITANSI PEREMPUAN TERHADAP RUMAH TANGGA PETANI DI KABUPATEN INDRAMAYU - Risnawati Risnawati; Ahmad Choibar Tridakusumah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Working as a migrant worker is one alternative for rural women to maintain the livelihoods of their agricultural households. Indramayu District is the second-largest contributor of female migrant workers in Indonesia and contributes to migrant households in the area of origin through social or economic remittances. Economically it can contribute to migrant households, one of which is used for agricultural investment. The purpose of this study is to analyze the contribution of remittances to agricultural investment. This research is a case study research using qualitative techniques. The selection of informants uses snowball techniques and through in-depth interviews. The results of this study indicate that the farmer's household conditions cannot be fulfilled only from agricultural and fishing activities (on-farm, off-farm, and non-farm). Being a female migrant worker has become a culture of rural communities because of the large number of remittances received making the migrant household's economy meet its needs. Remittances are used by migrant households for agricultural investment, such as boat purchases and agricultural land purchases.